CHARACTERISTIC OF FACTORS ASSOCIATED WITH ADMISSION TIME OF STROKE PATIENTS IN HOSPITAL - Tangkudung G; Pertiwi JM; Girsang R; Tongku AS; Ate A (Jurnal Sinaps, 2019)
Introduction: Stroke is a major cause of disability and death in Indonesia. Based on Riskesdas 2013 data, the incidence of stroke in North Sulawesi was ranked second after hypertension. Early management of stroke contributes to have better outcome. Our hospital data showed limited number of stroke patients who were admitted in early onset. We investigated factors related to admission time of stroke patients in RSUP Prof. dr. R. D Kandou Manado during 2015-2017. Method: This was a retrospective study using secondary data from stroke patients who met the eligibility. The statistical analysis was performed with Chi-square test with SPSS. Result: There were 1060 patients that were interviewed; only 0,5 % came in less than and equal 4 hours. There were 62% male. The mean age was 57,47 years. Of all patients, 47,1% patients had stroke ischemic and 52,8% patients had stroke hemorrhage. Those who delayed admission to the hospital beyond 4 hours were 98,3% patients did not recognize the urgency of immediate help for their symptoms and 99,8% patients traveled more than 10 km to reach our hospital. Conclusion: Approximately one-quarter of stroke patients correctly interpret their symptoms as representing a stroke. This knowledge was associated with delayed admission to the emergency department. Widespread public education of stroke-prone individuals may increase the proportion of patients eligible for new acute stroke treatments. Keywords: Admission time, stroke, knowledge.